Impact of adhesive and photoactivation method on sealant integrity and polymer network formation - Boniek Castillo Dutra Borges; Fabrício Lopes da Rocha Pereira; Roberta Caroline Bruschi Alonso; Rodivan Braz; Marcos Antônio Japiassú Resende Montes; Isauremi Vieira de Assunção Pinheiro; Alex José Souza dos Santos (Sociedade Brasileira de Pesquisa Odontológica, 2012)
We evaluated the influence of photoactivation method and hydrophobic resin (HR) application on the marginal and internal adaptation, hardness (KHN), and crosslink density (CLD) of a resin-based fissure sealant. Model fissures were created in bovine enamel fragments (n = 10) and sealed using one of the following protocols: no adhesive system + photoactivation of the sealant using continuous light (CL), no adhesive system + photoactivation of the sealant using the soft-start method (SS), HR + CL, or HR + SS. Marginal and internal gaps and KHN were assessed after storage in water for 24 h. The CLD was indirectly assessed by repeating the KHN measurement after 24 h of immersion in 100% ethanol. There was no difference among the samples with regard to marginal or internal adaptation. The KHN and CLD were similar for samples cured using either photoactivation method. Use of a hydrophobic resin prior to placement of fissure sealants and curing the sealant using the soft-start method may not provide any positive influence on integrity or crosslink density.